FATTY ACID PROFILE OF SMOKED TUNA PROCESSED WITH LIQUID SMOKES - DANIEL AMBROSIUS NICOLAS APITULEY; CINDY REGINA MAGDALENA LOPPIES (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
The research aimed to analyze the effect of several different liquid smokes on the fatty acid profile of smoked tuna. The liquid smokes were processed from coconut shells, sago bark, and Eucalyptus sp. Fatty acids were analyzed using gas chromatography and the lipid quality of smoked tuna was determined by computing the Atherogenic Index (AI) and Thrombogenic Index (TI). The results showed that the fatty acids profile of smoked tuna contained 28 fatty acids, 11 saturated and 17 unsaturated fatty acids. The polyunsaturated fatty acid (PUFA) content of smoked tuna was greater than the saturated fatty acid and monounsaturated fatty acid contents. The high ratio of PUFA-ω3/PUFA-ω6 and the low value of the AI and TI of the smoked tuna with liquid smoke from sago bark showed that its lipid quality was better than the lipid quality of control tuna and the other smoked tuna.